The influence of Malaysia's COVID-19 Movement Control Order (MCO) on energy consumption for residential areas in Peninsular Malaysia / Nur Azfahani Ahmad and Norazura Mizal Azzmi - Ahmad, Nur Azfahani; Mizal Azzmi, Norazura (2021)
Malaysia is currently experiencing the global COVID-19 pandemic which has impacted the Government to initiate the Movement Control Order (MCO). This order has commenced for several months (since March 2020) as a safety measure for the people in eliminating the spread of the virus. During this time, all sectors in Malaysia have been obligated to shut-down their operations and people were strictly advised to remain in their houses. Nevertheless, this enforcement has led to higher energy demands during the lock-down since people are staying at home 24-hours per day. Consequently, this paper investigates the pattern of energy consumption for residential areas by collecting information from over 100 families throughout Peninsular Malaysia. Selected households were chosen from each state in Peninsular Malaysia through random sampling and empirical analysis were obtained based on types of appliances and duration of use. The results showed that the level of energy consumption hikes by 20% to 50% since people used their domestic electrical appliances more than usual. This study has proven that energy consumption levels have significantly increased during the MCO